2009
DOI: 10.1007/s00775-009-0503-y
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Cu(I)–π interaction fine-tunes the metal binding properties of the bacterial metallochaperone CusF

Abstract: The periplasmic metallochaperone CusF coordinates Cu(I) and Ag(I) through a unique site consisting of a Met 2 His motif as well as a Cu(I)-π interaction between a nearby tryptophan, W44, and the metal ion. Through mutational analyses we investigate here the role that W44 in CusF plays in metal coordination. Nuclear magnetic resonance spectra show that the specificity of CusF for Cu(I) and Ag(I) is not altered by mutation of W44. X-ray absorption studies reveal that W44 protects the bound Cu(I) from oxidation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
43
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 24 publications
7
43
0
Order By: Relevance
“…CusF, although having a metal-binding affinity comparable to CusB (46,47), is not essential for CusCBA assembly, as we showed (Fig. 1C).…”
Section: Discussionsupporting
confidence: 69%
“…CusF, although having a metal-binding affinity comparable to CusB (46,47), is not essential for CusCBA assembly, as we showed (Fig. 1C).…”
Section: Discussionsupporting
confidence: 69%
“…4,5). 9 Our calculations found that Cu + was bound to His36, Met44, Met47 and Met49 residues in a distorted tetrahedral arrangement as shown in Fig. 3.…”
mentioning
confidence: 62%
“…7 Experiments by Loftin et al have suggested that Trp44 protects Cu + /Ag + from oxidative stress in the periplasm. 9 The role of the cation-π interaction in the function of CusF remains unclear as a W44M mutation exists in 25% of CusF proteins. The W44M mutant CusF is known to have a higher binding affinity for Cu + 7,9 .…”
mentioning
confidence: 99%
See 2 more Smart Citations